(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article outlines the methodology for developing professional competencies of future teachers through collaborative education technology. The approach emphasizes the use of collaborative learning techniques to enhance the skill set of prospective educators. By leveraging technology to facilitate group work and interactive learning experiences, this methodology aims to prepare teachers for the challenges of modern educational environments. The article highlights the importance of integrating collaborative education technology into teacher training programs to foster the development of essential competencies such as communication, teamwork, problem-solving, and critical thinking. The methodology described in this article offers a structured framework for incorporating collaborative learning strategies into teacher education curricula, ultimately equipping future educators with the necessary skills to excel in their profession